STRATEGI PEMASARAN PAKET WISATA DALAM MENINGKATKAN JUMLAH KUNJUNGAN WISATAWAN DI DESA WISATA TISTA, KERAMBITAN, TABANAN - Aldu, Maria Pricilla Cahyavika; Sudana, I Putu; Dewi, LGLK. (Jurnal IPTA (Industri Perjalanan Wisata); Vol 11 No 2 (2023): Jurnal IPTA (December 2023)DO - 10.24843/IPTA.2023.v11.i02.p15, 2023)
Tista tourism village is one of the tourism villages located in Kerambitan District, Tabanan Regency, Bali. This village sells various tour packages and has been designated as a tourist village since 2016 but tourist visits are still relatively small. Therefore, this research was conducted to find out the marketing strategy of the Tista tourism village tour package in increasing tourist visits.The data analysis technique is internal environment using 7P Marketing Mix analysis and the external environment using market, competitor, government, technology, and economic analysis and SWOT. Data types use qualitative and quantitative data. Data sources use primary and secondary data sources. Data collection techniques using observation, interviews, documentation, literature studies, and distributing questionnaires. The data analysis technique uses descriptive qualitative. The results of the study used 18 internal indicators and 7 external indicators, then obtained 14 strengthes, 4 weaknesses, 4 opportunities, and 3 threats. Based on the results of data processing, it’s known that the total IFAS value is 3.10 and the EFAS value is 3.02 so that the position of the Tista tourism village tour package is in cell V, namely Growth Strategy/Stability Strategy with concentration through horizontal integration. A suitable strategy is a strategy that can prevent profit loss and loss of profit.